Young Children and Their Parents Perspectives from Psychoanalytic Infant Observation - Diem-Wille, Gertraud (Karnac, 2014)
The book describes the psychoanalytic perspective of development of theparent-infant relationship in the first three years of life.The importance of the earliest experiences of the child in the interaction with the parents shape sthe emerging personality of the child. The book follows the life of a child from birth to the third year.